Faktor- Faktor Yang Mempengaruhi Pelaksanaan Dokumentasi Keperawatan Di Ruang Rawat Inap Rumah Sakit Islam Hj. Siti Muniroh Tasikmalaya - Asep Riyana; Arip Rahman (Universitas Galuh, 2023)
Nursing documentation is evidence of recording and reporting owned by nurses in carrying out nursing care, which is useful for the benefit of clients, nurses and the health team in providing health services. The research objective was to describe the factors that influence the implementation of nursing care documentation in the Inpatient Room of Hj Islam Hospital. Siti Muniroh Tasikmalaya. The research method used is descriptive research. The sample in this study were 33 nurses. The results of the study found that most of the nurses at the Hospital Islam Hj. Siti Muniroh Tasikmalaya has sufficient knowledge about nursing care documentation (51.52%). The number of nurses in the Islamic Hospital Hj. Siti Muniroh Tasikmalaya stated that most of the rooms did not meet the needs of three rooms (60%). Nurse at Inpatient Hospital Islam Hj. Siti Muniroh Tasikmalaya mostly carried out nursing care documentation procedures (57.58%). Nurse at Inpatient Hospital Islam Hj. Siti Muniroh Tasikmalaya stated that most of the nursing supervision was carried out (66.67%). Based on the results of the research, the authors suggest that planning for the needs of nurses is adjusted to the workload of nurses and the level of dependency of clients, not based on the number of beds in the hospital.